Clima escolar y agresividad en estudiantes de secundaria de la Institución Educativa N° 64478 Bilingüe Intercultural Mariscal Ramón Castilla 2024 - Parente Careca, Jonh (2025)
The aim of the study was to determine the relationship between school climate and aggressiveness among secondary school students at Educational Institution No. 64478 Bilingual Intercultural Mariscal Ramón Castilla (Bellavista Callarú, Peru, 2023). The approach was quantitative, with a relational, non-experimental design. The sample consisted of 150 students who completed validated surveys: the Gutiérrez Marfileño School Climate Scale (dimensions: general coexistence climate and satisfaction/fulfillment of expectations) and the Buss Aggressiveness Questionnaire (dimensions: physical, verbal, anger, and hostility). The data were analyzed using SPSS and JASP, employing descriptive statistics and Kendall’s Tau B coefficient for ordinal correlations. Descriptive results revealed that in a good school climate, 33% of the students were non-aggressive, whereas in poor school climates, 13% displayed aggressiveness. Additionally, the inferential results showed strong and significant positive correlations between the variables: General school climate: Tau B = 0,926 (p < 0,001). General coexistence climate: Tau B = 0,802 (p < 0,001). Satisfaction/fulfillment of expectations: Tau B = 0,827 (p < 0,001) Thus, these results indicate that a good school climate is associated with lower levels of aggressiveness, which supports the general hypothesis. The study also emphasizes the importance of creating inclusive educational environments aimed at reducing aggressive behavior among students, involving both educational policies and school management strategies. Limitations include the study’s relational (non-causal) design and the local sample, as well as the suggestion to conduct future research in broader contexts.